Studi Komparasi Kuantitas Bivalvia pada Zona Intertidal di Pantai Ntana Kabupaten Bima sebagai Upaya Penyusunan Brosur Konservasi - Rahmantyah, Sri Samira (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2023)
Bivalves belong to the Phylum mollusca. Bivalve are found and live in the Intertidal area. Ntana Beach is the easiest area and has the most interaction with human activities, because this area is a transitional area between aquatic ecosystems and land ecosystems. This study aims to: 1) identify the types of bivalves that make up the Intertidal zone on the Ntana coast, Bima Regency; 2) analyzing the abundance, diversity index, and evenness of Bivalvia in the Intertidal zone on the Ntana coast, Bima Regency; 3) describe the population of bivalve species that dominate the Intertidal zone on the Ntana coast, Bima Regency; 4) analyzing the abundance of bivalves in the sandy, muddy and rocky substrate areas on the Ntana beach, Bima Regency; 5) analyzing the diversity of bivalve species in the area of ​​sandy substrate, muddy substrate, and coral substrate on the Ntana beach, Bima Regency; 6) knowing the differences in the dominance of Bivalvia in the sandy, muddy and rocky substrate areas on the Ntana beach, Bima Regency; and 7) to develop research results on a comparative study of the quantity of bivalves in the intertidal zone on the Ntana coast, Bima district as an effort to prepare a conservation brochure. This type of research is descriptive comparative. Sampling used a 1x1 M plot. The results showed that as many as 540 individual bivalves consisting of 15 species were found on the Ntana beach, Bima district. 15 species of bivalves found include Anadara antiquata, Anadara granosa, Anadara brasilliana, Panopea generosa, Fausta pultenei, Dosina crebra, Eurytellina alternate, Dosina discus, Nactula acuta, Gafrarium divaricatum, Dosinia exoleta, Caestoderma edule, Gafrarium disparm, Cyclocardia ventricosa, and Crassostrea gigas. The abundance on sandy and silty substrates is categorized as moderate, whereas on coral substrates it is categorized as low. Species diversity on rocky substrates is less, whereas on muddy and sandy substrates each has a fairly high level of species diversity. The evenness value on sandy and muddy substrates is close to zero (0), so that the evenness of Bivalvia species on both substrates is not evenly distributed. There are no species that dominate other species because D <0.5. The average value of the brochure validation test is 75.4%, with this result, the brochures that have been compiled are in the good category and do not need to be revised.